Inhibition of ASCT2 is essential in all‐trans retinoic acid‐induced reduction of adipogenesis in 3T3‐L1 cells. Issue 1 (2nd July 2015) - Takahashi, Katsuhiko; Uchida, Natsumi; Kitanaka, Chisato; Sagara, Chiaki; Imai, Masahiko; Takahashi, Noriko
Abstract : Vitamin A has preventive effects on obesity. All‐ trans retinoic acid (ATRA), the active form of vitamin A, inhibits lipid accumulation in 3T3‐L1 cells in an experimental adipogenesis model. We found that ATRA suppressed up‐regulation of the amino acid transporter, Asct2, in adipogenerating 3T3‐L1 cells. We observed that Asct2 was up‐regulated at 1 day after adipogenesis stimuli. The Asct2 inhibitorl ‐γ‐glutamyl‐ p ‐nitroanilide (GPNA) decreased lipid accumulation. Glutamine‐free conditions also suppressed adipogenesis. Suppression of adipogenesis by ATRA may be through Asct2 reduction. These results indicate that Asct2 could be a target for obesity prevention and treatment. Abstract : Asct2, an amino acid transporter, could be a target for obesity prevention and treatment. All‐ trans retinoic acid suppresses upregulation of Asct2 during adipogenesis of 3T3‐L1 cells. The Asct2 inhibitor, l ‐γ‐glutamyl‐ p ‐nitroanilide, suppresses adipogenesis at early time points. Treatment withl ‐γ‐glutamyl‐ p ‐nitroanilide suppresses adipogenesis more effectively thanl ‐glutamine‐deficient conditions.